PELAKSANAAN FUNGSI PENGADILAN NIAGA DALAM PENYELESAIAN PERKARA KEPAILITAN (Suatu Analisis di Pengadilan Niaga Medan) - M. Jazuri, Dahlan, Yusri Z. Abidin. (Jurnal Ilmu Hukum, 2013)
Abstract: In May 1997 the monetary crisis that hit many parts state of the world including Indonesia. Due to the monetary crisis in Indonesia are many companies that went bankrupt. As a company typically known for their activities in need of loan funds from some other company that is known by the term debtor and creditors. As a result of this crisis is often Debtors unable to pay off his debts. To prevent looting and seize each other among some creditors will require the existence of a legal rule that can be used in a speedy, fair, open and efficient. So that the government establish a legal rule that is The Government Regulation as Replacement Act Number 1, 1998, then passed by the Act Number 4, 1998 and and revised to be the Act Number 37, 2004 on Bankruptcy and Suspension of Payment (PKPU). Under Article 7 the Act Number 37, 2004 is authorized to hear and rule on cases of bankruptcy and Suspension of Payment is Trading Court that is within GeneralCourt. Based the provisions of Article 281 paragraph (1) The Government Regulation as Replacement Act Number 1, 1998 Jo Act Number 4, 1998 was first established at the Central Jakarta District Court. Furthermore, based on the Presidential Decree Number 97, 1999, established of 5 (five) other Trading Court, they are the Trading Court of Ujung Pandang (Makassar), the Trading Court of Medan, the Trading Court of Surabaya and the Trading Court of Semarang. In fact, with the revisions to the Bankruptcy Rules of the Trading Court of Medan capable of resolving Trading disputes in a fair, fast, open and effective? This paper aims at reviewing the existing reality in the implementation of the Bankruptcy Act in the Trading Court of Medan whether to provide legal certainty as expected by the Bankruptcy Act to the business world for both the debtor and creditors and also for the people of Indonesia in general. Are there any constraints are found and how to handle it. To obtain the data in this study conducted with 2 (two) ways, namely: Library Research and Field Research. The literature research carried out in order to obtain secondary data, through a review of legislation, literature, literature, research works, journal of legal experts who have anything to do with this research. While field studies to obtain primary data, obtained by conducting interviews with informants and respondents. The results showed that the Trading Court of Medan has been carrying out the applicable provisions of the act number 37, 2004 on Bankruptcy and Suspension of Payment. but there are some provisions that are difficult to be implemented such as the calling period of the parties and the examination process. In addition there were a few rules in the Bankruptcy Act and the Suspension of Payment are also a couple of conflicting rules in the Act which conflict with other act. Human Resources is also a barrier. Limitations of judges and court staff in the almost the trial schedule another case resulted in judges and court staff should be smart divide the trial schedule. To an external court advocates and curator are still very few professional who has a certificate in the completion of the bankruptcy case and understand the rules of bankruptcy. Substantial costs are also an obstacle for creditors to use bankruptcy institution. The Government Regulation to issue the implementing rules supporting this bankruptcy case is still low, such as the implementing regulation of the effort to force the body (Gijzeling) which until now has not been published. The results showed that the Trading Court of Medan has been carrying out the applicable provisions of the Act Number 37, 2004 on Bankruptcy and Suspension of Payment, but there are some rules that take very different, especially regarding the limits of the parties and calls on the definition of